The Impact of Religious Practices on the Resilience and Post-Traumatic Growth of Adolescents - Yuliyanti, Yusvina; Shodiq, Sadam Fajar (citeus, 2025)
Resilience and post-traumatic growth play crucial roles in the development of adolescents, particularly when they encounter diverse obstacles in life. The objective of this study is to investigate the impact of religious practices on resilience and experience personal growth after experiencing trauma in adolescents. This research employs a quantitative methodology grounded on a positivist framework. Data were gathered using a simple random sampling method including 218 Muslim teenagers in Yogyakarta, Indonesia who had encountered stressful incidents in the preceding year. Statistical analysis was employed to examine the correlation between variables. This research illustrates that religious practices may serve as a substantial source of resilience for teenagers in managing trauma. Engagement in religious activities enhances resilience and fosters healthy development. These findings indicate the need for the amalgamation of spiritual support and psychological therapies to facilitate teenage rehabilitation.